ASSESSMENT OF THE RATE AND CHARACTERISTICS OF TREATMENT CHANGES FOLLOWING RENAL BIOPSY RESULTS IN PATIENTS WITH GLOMERULAR DISEASES (Vietnam Journal of Community Medicine, 2026)
Renal biopsy is the gold standard in the diagnosis of glomerular diseases, helping to guide and individualize treatment, especially treatment with immunosuppressive drugs. Objective: To evaluate the rate and characteristics of changes in indications for immunosuppressive drug treatment after renal biopsy results in patients with glomerular diseases. Methods: Observational cohort. Location: Center for Nephrology, Urology and Dialysis, Bach Mai Hospital. Time: From January 2024 to February 2026. Results: A total of 554 patients were studied. The rate of patients whose immunosuppressive drug treatment was changed after renal biopsy results was 46%, and there were differences among groups of glomerular diseases. The rate of change was 100% in rapidly progressive glomerulonephritis, 74.5% in lupus nephritis, 44.7% in IgA nephropathy, 37.3% in nephrotic syndrome, and 35.1% in other glomerular diseases. Among the patients whose treatment was changed, 31.8% were started on immunosuppressive drugs, 56.9% had their immunosuppressive drug treatment intensified, 3.1% had the treatment intensity reduced, 5.1% were switched to another regimen, and 3.1% discontinued immunosuppressive drugs. Conclusion: The rate of patients whose immunosuppressive drug treatment was changed after renal biopsy results was 46%, of whom the majority were started on or had their immunosuppressive drug treatment intensified.
Keywords: Treatment modification, renal biopsy, glomerular disease